“Do we even have a voice?” Health providers’ perspective on the patient accommodation strategies in Bangladesh - Md. Ruhul Kabir; Kara Chan (PLoS ONE, 2022)
Objective In a resource-constrained setting like Bangladesh, effective patient-provider communication is critical to the delivery of maternal healthcare services. Using communication accommodation theory, this study tried to understand how providers perceive, engage, and accommodate patients’ needs in maternity wards. Methods This qualitative exploratory study used a semi-structured interview guide to conduct in-depth face-to-face interviews of ten healthcare providers in two government-funded public health facilities in Bangladesh. The interview data were analyzed using MAXQDA 2020 software. Results The thematic analyses revealed that nurses and midwives faced conceivable neglect from patients and their attendees due to possible service and facility constraints, indicating their low status and control within the service operation. Despite efforts to address patients’ emotional and psychological concerns, providers appear to avoid (divergence strategy) confronting patients and their irate visitors. Unimodal convergence emerged when providers accepted patients’ arguments about the systematic inadequacy of service facilities. Providers have employed interpretability tactics to communicate medical opinions and applied nonverbal cues where necessary. Conclusion A lack of open communication between healthcare providers and patients necessitated various forms of accommodation. Integrated strategies addressing service restrictions and initiatives fostering patient understanding and cooperation may improve patient-provider communication.